2013
DOI: 10.1002/adem.201300138
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of the Percolating Intermetallic Microstructure of High Pressure Die Cast AZ91 Alloy

Abstract: The intermetallic microstructure in two representative regions of the cross section, the corner and the core, of a cast-to-shape tensile specimen was studied. Available 3D data of the intermetallic, obtained with focused dual ion beam tomography, were incorporated into a finite element code to simulate the deformation behavior. The modeling reveals a high structural compliance at both the corner and the core, akin to the bending-dominated behavior of cellular foams. The high compliance suggests that the percol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Since the major intermetallic phases in AJ52 and the AE alloys tend to have a lamellar structure, it is likely that the morphology of the intermetallic phase also plays a role in influencing the alloy strength, i.e., the strengthening contribution is higher when the intermetallic phase is divorced and continuous rather than being lamellar. This difference can be explained by the additional strengthening effect from the percolating network of the intermetallic phase, which was proposed recently by Zhang et al [51,52] Based on dual-beam focused-ion beam (FIB) tomography and finite element analysis (FEA), Zhang et al [51,52] provided detailed insight into the 3D configuration and deformation behavior of the percolating intermetallic phases in diecast Mg-Al and Mg-RE alloys. They found that the intermetallic phases with profuse spatial interconnection have a higher strengthening effect than what would be expected through dispersion hardening, i.e., isolated particles with the same volume fraction.…”
Section: A Microstructure/tensile Properties Relationshipmentioning
confidence: 96%
“…Since the major intermetallic phases in AJ52 and the AE alloys tend to have a lamellar structure, it is likely that the morphology of the intermetallic phase also plays a role in influencing the alloy strength, i.e., the strengthening contribution is higher when the intermetallic phase is divorced and continuous rather than being lamellar. This difference can be explained by the additional strengthening effect from the percolating network of the intermetallic phase, which was proposed recently by Zhang et al [51,52] Based on dual-beam focused-ion beam (FIB) tomography and finite element analysis (FEA), Zhang et al [51,52] provided detailed insight into the 3D configuration and deformation behavior of the percolating intermetallic phases in diecast Mg-Al and Mg-RE alloys. They found that the intermetallic phases with profuse spatial interconnection have a higher strengthening effect than what would be expected through dispersion hardening, i.e., isolated particles with the same volume fraction.…”
Section: A Microstructure/tensile Properties Relationshipmentioning
confidence: 96%
“…The spatially interconnected eutectic microstructure that forms in most High Pressure Die Cast (HPDC) Mg-alloys [10,[110][111][112][113] has been shown to introduce hardening effects ranging from a few MPa in AZ91 to ~40 MPa in some Mg-RE alloys. In a Mg-RE alloy, strengthening of the α-Mg matrix in which the eutectic structure was embedded, a ternary addition [112] 4 and 5.…”
Section: Percolating Eutectic Microstructurementioning
confidence: 99%
“…[1][2][3][4][5] An example is given in Figure 1, where lighter color represents the network of eutectic (a-Mg)-Mg 12 Ce in a HPDC Mg-0.51 at% Ce alloy, locating at the grain boundary between adjacent grains of a-Mg matrix. [1][2][3][4][5] An example is given in Figure 1, where lighter color represents the network of eutectic (a-Mg)-Mg 12 Ce in a HPDC Mg-0.51 at% Ce alloy, locating at the grain boundary between adjacent grains of a-Mg matrix.…”
Section: Experimental Observationmentioning
confidence: 99%
“…The establishment of a micromechanical model is based on microstructural observations that intermetallic/eutectics are interconnected in a series of HPDC and sand squeeze-cast Mg alloys, cf. [1][2][3][4][5] An example is given in Figure 1, where lighter color represents the network of eutectic (a-Mg)-Mg 12 Ce in a HPDC Mg-0.51 at% Ce alloy, locating at the grain boundary between adjacent grains of a-Mg matrix.…”
Section: Experimental Observationmentioning
confidence: 99%
See 1 more Smart Citation